In situ nanoparticle embedding for authentication of epoxy composites - Pansare, Amol V.; Khairkar, Shyam R.; Shedge, Amol A.; Chhatre, Shraddha Y.; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials, 2018)
In situ reduction of chloroauric acid inside an amine-cured epoxy matrix leads to formation of gold nanoparticles which are embedded inside the part. This phenomenon is leveraged to design an authentication system for composites wherein the particles are embedded spatially and are invisible to the naked eye. Under UV light, the particles diffract light and create an easily visible path. The particles penetrate inside the part and create a permanent, cost-effective, tamper-proof code. The advantage of this technique is that this authentication system can be built in composite parts after fabrication of the composite structure. As very small amount (nanograms) of particles are present in the part, negligible change in the thermal characteristics of the parent matrix is observed. The particles can be embedded easily in carbon fiber as well as glass fiber reinforced epoxy structures.
Keywords: authentication; barcoding; composites; embedded nanoparticles; Epoxy

X-ray fluorescence-based spray-on ``elemental barcodes'' - Pansare, Amol V.; Terrasi, Giovanni P.; Pansare, Shubham V.; Khairkar, Shyam; Shedge, Amol A.; Zote, Santosh W.; Chhatre, Shraddha; Barbezat, Michael; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials Technologies, 2025)
A novel spray-on elemental barcode technology is reported for the secure, permanent, and tamper-proof identification of polymeric and fiber-reinforced composite materials. This system utilizes the in situ reduction of metal salts to nanoparticles embedded within a polymer matrix, creating a unique barcode that is detectable through X-ray fluorescence (XRF). The barcode's composition is based on the metallic nanoparticle mixture and offers a semi-quantitative, non-destructive, and thermally stable method for material authentication. The process is straightforward, involving the manual application of metal salt solutions followed by mild heating, ensuring no significant alteration to the material's properties. The barcodes can be read through protective coatings or paints and are robust even under extreme conditions, such as high temperatures. This low-cost method does not introduce additional manufacturing steps and demonstrates significant potential for anti-counterfeiting and lifecycle tracking in various industries. Moreover, with an information density of up to 12 bits mm-1, this elemental barcode significantly surpasses the data storage capabilities of traditional optical barcodes. This approach holds promise for broad substrate applicability and can be expanded to other metals and reduction protocols, making it versatile for diverse material applications.
Keywords: authentication; barcoding; embedded nanoparticles; epoxy thermosets; fiber-reinforced composite; in situ reduction